Synthesis of Nature-Inspired Medium-Sized Fused Heterocycles from Amino Acids - Ventosa-Andrés, Pilar; La-Venia, Agustina; Ripoll, Carlos Alfonso Barea; Hradilová, Ludmila; Krchňák, Viktor (Chemistry (Weinheim an der Bergstrasse, Germany), 2015)
Herein, we describe the synthesis of molecular scaffolds consisting of medium-sized fused heterocycles using amino acids, which are some of the most useful building blocks used by nature as well as chemists to create structural diversity. The acyclic precursors were assembled by using traditional Merrifield solid-phase peptide synthesis, and cyclization was carried out through acid-mediated tandem endocyclic N-acyliminium ion formation, followed by nucleophilic addition with internal nucleophiles. The synthesis of molecular scaffolds consisting of seven-, eight-, and nine-membered rings proceeded with full stereocontrol of the newly generated stereogenic center in most cases.
Keywords: cyclization; molekulární struktura; aminokyseliny; Heterocyclic Compounds; Cyclization; cyklizace; heterocyklické sloučeniny; Molecular Structure; solid-phase synthesis; stereoizomerie; drug discovery; fused-ring systems; Stereoisomerism; Amino Acids; regioselectivity